Sources of Funding for Socially Useful Projects Managed by Non-governmental Organization in Poland - Izabela TUREK (Communications of International Proceedings, 2022)
In Poland and worldwide there is a growing importance of non-governmental organisations, which by their very nature carry out socially useful tasks. The main purpose of the existence of such organisations is the implementation of projects perceived as socially useful. These entities are not obliged to generate profit. What is more important in their functioning is to fill the gap created as a result of insufficiently effective government mechanisms in responding to social needs and the lack of interest in, or lack of opportunities for, carrying out certain social tasks on the part of private entities. The research undertaken in the article was carried out in a group of non-governmental organisations operating in Poland, whose statutory objectives focus on supporting economic development and entrepreneurship and which were granted the status of public benefit organisations. The main aim of the research was to identify and anayze the basic sources of financing projects managed by these organisations. As shown by the conducted research, NGOs rely to a large extent on external sources of financing from donating 1% of the PIT and public funds - in total more than 80% of activities are financed from these sources. Therefore, the possibility of implementation of these projects to a large extent depends on the amount of raised external funds.
Keywords: Non-government organization (NGO); socially useful projects; project management; sources of funding.